A new species of Yphthimoides (Lepidoptera: Nymphalidae: Satyrinae) from the southern Atlantic forest region - Freitas, André V. L.; Kaminski, Lucas A.; Mielke, Olaf H. H.; Barbosa, Eduardo P.; Silva-Brandão, Karina L. (Zootaxa, 2012)
This paper describes a new, abundant and widespread species of Yphthimoides Forster from the Atlantic forests of southern Brazil, Paraguay, and northern Argentina (Misiones) in open and secondary vegetation and forest edges. Adult and immature stage morphology is described, molecular data are provided, and the placement of the new species within the genus Yphthimoides is discussed.